PERHITUNGAN MANHOURS DAN KEBUTUHAN MANPOWER NON-DESTRUCTIVE TEST PADA WHEEL AND BRAKE SHOP MENGGUNAKAN METODE VOGEL’S APPROXIMATION METHOD (VAM) - Hardanny, Danny; Mufti Arifin; Ayu Martina (FTK UNSURYA, 2025)
An airplane is a means of air transportation used to transport passengers and goods from one place to another. Just like other transportation in general, aircraft also require maintenance. One of the aircraft maintenance activities is maintenance on the Main Wheel and Brake of the aircraft which has an important role on the aircraft. In Wheel and Brake maintenance is examined in detail with various methods, one of the methods used in Wheel and Brake maintenance is the Non-Destructive Test (NDT) method. In this case, to carry out the Non-Destructive Test inspection the company must be able to distribute Manpower needs with a good and appropriate Manhour. This study aims to optimize the allocation of manpower and time (manhour) in the implementation of Non-Destructive Test (NDT) inspections at the Wheel and Brake Shop using the Vogel Approximation Method (VAM), resulting in savings in human resources and increased efficiency in the implementation of Non-Destructive Test (NDT) inspections at the Wheel and Brake Shop. From the results of the analysis, it can be seen the distribution of manhour on various NDT component jobs and it is found that using the Vogel's approximation method (VAM) calculation results in 588.3 manhours. it is known that by using the VAM method the difference obtained is 47.7 manhours faster than the actual data which is 636 manhours with a percentage of 13.2% faster.